TUNDANG ORAL ART AS AN EDUCATIONAL MEDIUM: A STRUCTURAL AND FUNCTIONAL PERSPECTIVE - Wulan, Adisti Primi; Yuda, Ramadhan Kusuma (JURNAL KONFIKS, 2025)
Tundang art is a form of oral literature from the Malay community in West Kalimantan that contains educational, moral, religious, and cultural values passed down through generations. This study aims to reveal the structure and function of tundang art as a traditional educational medium within the Malay society, focusing on tundang verses themed around the 27th Musabaqah Tilawatil Quran (MTQ) of West Kalimantan Province. The research employs a structural and functional approach with a qualitative descriptive method. Data were collected through documentation, transcription, and text analysis of 15 purposively selected tundang verses. The results show that structurally, the tundang verses have a consistent rhyme pattern (a-b-a-b), consist of four lines per stanza, each line containing 6–9 syllables, with a division between the sampiran (opening) and isi (content) reflecting the typology of Malay pantun. Functionally, tundang serves as a medium for moral education (instilling ethics and politeness), religious education (strengthening Islamic values), cultural education (preserving local customs and traditions), and entertainment (engaging through rhythm and wordplay). This study concludes that tundang not only functions as a performing art but also as a rich educational vehicle, making it highly potential for development in literature learning based on local wisdom.